Implementation of Typography Art as a Craft with Eco Print Technique - Maria Cornelia Wara Candrasari; Rahmawati Rahmawati; Febby Bunga Permata Sumardi (Jurnal Pendidikan Abad Ke-21, 2025)
The research uses a qualitative method based on research-led practice to explore capital typography (uppercase letters) as a medium for art creation as well as cultural education. The focus of the research includes analysis of motifs, techniques, colors, and materials, with data sources obtained from sources (craftsmen, designers, cultural experts), literature studies, and visual documentation. Data collection was conducted through observation, in-depth interviews, questionnaires (target: students/community), and creative experiments.  The ecoprint technique, or eco-printing, is a method of dyeing fabric with natural dyes. In this study, the ecoprint technique, which applies natural dyes to fabric, focused on works featuring capital typography—particularly complex letters like G, Q, and O—to emphasize the value of precision and patience in the craft. The technical challenges of letter formation were utilized as a means of recognizing local wisdom, with each stage documented and critically reflected upon. The resulting work is not only assessed in terms of aesthetics, but also its educational function, namely as a cultural learning tool through a visual approach.  Validation involved design experts, educators, and cultural communities to ensure the suitability of the work to the social context. The results show that capital typography can be an effective bridge between art and cultural education, with applicable outputs such as interactive workshops or exhibitions. Audience surveys revealed an increased understanding of cultural values after interaction with the works.  This research contributes to the field of cultural preservation through design innovation and a fun, non-formal education model. The implication is that a similar approach can be replicated for other cultural elements, strengthening local identity as well as attracting the younger generation.